CASQ2 variants in Chinese children with catecholaminergic polymorphic ventricular tachycardia. Issue 11 (3rd September 2019) - Li, Qirui; Guo, Ruolan; Gao, Lu; Cui, Lang; Zhao, Zhihui; Yu, Xia; Yuan, Yue; Xu, Xiwei
Abstract: Background: Biallelic variants of the CASQ2 are known to cause the autosomal recessive form of catecholaminergic polymorphic ventricular tachycardia (CPVT), an inherited disease that predisposes young individuals to syncope and sudden cardiac death. To date, only about 24 CASQ2 variants have been reported in association with CPVT pathogenesis; furthermore, studies in Asians, especially in the Chinese population, are relatively rare. The aim of this study was to detect CASQ2 variants in Chinese patients with CPVT. Methods: We used targeted next‐generation sequencing (NGS) to identify CASQ2 variants in Chinese patients with CPVT. A screening process was performed to prioritize rare variants of potential functional significance. Sanger sequencing was conducted to conform the candidate variants and determine the parental origin. Results: We identified seven different CASQ2 variants, of which three (c.1074_1075delinsC, c.1175_1178delACAG, and c.838+1G>A) have not been previously reported. The variants exhibited autosomal recessive inheritance, and were detected in four unrelated Chinese families with CPVT. They included a nonsense variant c.97C>T (p.R33*) and a missense variant c.748C>T (p.R250C) in Family 1 with three CPVT patients; two heterozygous frameshift variants, c.1074_1075delinsC (p.G359Afs*12) and c.1175_1178delACAG (p.D392Vfs*84), in Family 2 with one CPVT patient; one pathogenic homozygous variant c.98G>A (p.R33Q) of CASQ2 in the CPVT patient of Family 3; and two heterozygous splicing variants, (c.532+1G>A) and (c.838+1G>A), in Family 4 with one CPVT patient. Conclusion: To our knowledge, this is the first systematic study of Chinese children with CASQ2 variants. Our work further expands the genetic spectrum of CASQ2 ‐associated CPVT. Abstract : We identify four novel mutations in the CASQ2 that lead to a rare autosomal recessive type of catecholaminergic polymorphic ventricular tachycardia (CPVT), which expand the genotypic spectrum of CPVT. It provides a molecular basis for study into the mechanism of CASQ2 mutations in Chinese patients with CPVT.